Letr/ação: teatro e cinema na sala de aula possível proposta para revolução - Simon de Oliveira Martins (2022)
The present work brings the experience of a collective creative artistic process, in audiovisual language, as an anti-oppressive didactic practice. It is intended, through the production of a film, together with the fifth year students of a public school in the city of Belo Horizonte, to point out the pedagogical factors of this process, relating them to the discussions about filmmaking in the school space. To do so, I will start from Conceição Evaristo's idea of "escrevivência" (2020) to develop the video script through theatrical dynamics, which produce a rereading, with a decolonial bias, of George Orwell's Animal Farm (1945). From an analytical point of view, I intend to establish dialogues between the proposed practice and the concepts of intersectionality, as discussed by Carla Akotirene (2019), and the pedagogy of autonomy, by Paulo Freire (1996).